Pulmonary drug delivery: A review on nanocarriers for antibacterial chemotherapy - Moreno Sastre, M. (2015)
As the WHO stated, lower respiratory infections are the third leading cause of death. In addition, it is remarkable that antimicrobial resistance represents a huge threat. Thus, new therapeutic weapons are required. Among the possible alternatives, antibiotic encapsulation in nanoparticles has gained much attention in terms of improved tolerability, activity and ability to combat the resistance mechanisms of bacteria. In this regard, this reviewarticle focuses on the latest nanocarrier approaches for inhalatory therapy of antibiotics. First, the technology related to lung disposition will be reviewed. Then, nanocarrier systems will be introduced and the challenges required to perform adequate pulmonary deposition analysed. In the following part, drug delivery systems (DDSs) on the market or in clinical trials are described and, finally, new approaches of nanoparticles that have reached preclinical stage are enumerated. Altogether, this review aims at gathering together the novel nanosystems for anti-infectious therapy, underlining the potential of DDSs to improve and optimize currently available antibiotic therapies in the context of lung infections.